Vivienda Colectiva en zonas no consolidadas, Cantón Riobamba - Escudero Moyón, Michael Ronaldo (2025)
The research addresses the housing problem in unconsolidated areas of Riobamba, caused by rapid urban growth, rural-urban migration, and a lack of adequate planning. A collective housing model is proposed to densify the five unconsolidated areas designated by Riobamba’s PDOT, optimizing land use and increasing green areas. Through a multiscale analysis (macro, meso, and micro), San Miguel de Tapi was identified as the intervention area, considering socioeconomic, demographic, regulatory, and physical characteristics. The study reviews the background of the housing deficit in Riobamba, theoretical aspects, and similar national and international cases at the urban and architectural level, highlighting collective housing. Methodologically, it combines urban diagnosis, analysis of references, weighting of indicators, and architectural design, prioritizing the diversification of typologies to meet the needs of low-income families. It highlights that integrated urban planning and the development of collective housing can reduce inequalities, guarantee fundamental rights, and curb disorderly expansion into rural areas. The project proposes doubling housing density from 60 to 120 inhabitants per hectare by 2030, promoting balanced, resilient, and sustainable growth. It concludes with a project featuring a green center that allows for social interaction and recreation, diversity of use by mixing residential, commercial, and amenities, transition areas, and public-private connections through different zones and clear volumetry at the formal level and through the use of identifying materials in each zone.